2012
DOI: 10.1017/s0007114511006751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purified β-glucans derived fromLaminaria digitata,Laminaria hyperboreaandSaccharomyces cerevisiaeon piglet performance, selected bacterial populations, volatile fatty acids and pro-inflammatory cytokines in the gastrointestinal tract of pigs

Abstract: b-Glucans have been identified as natural biomolecules with immunomodulatory activity. The first objective of the present study was to compare the effects of purified b-glucans derived from Laminaria digitata, L. hyperborea and Saccharomyces cerevisiae on piglet performance, selected bacterial populations and intestinal volatile fatty acid (VFA) production. The second aim was to compare the gene expression profiles of the markers of pro-and anti-inflammation in both unchallenged and lipopolysaccharide (LPS)-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 39 publications
(52 reference statements)
7
97
3
Order By: Relevance
“…Kogan and Kocher found that SCCWE polysaccharides (mainly β -glucan) can modulate immunity and the absorption of mycotoxin, prevent the adhesion and dissemination of bacteria, and finally improve the health of pigs [10]. Additionally, Sweeney et al showed that oral administration of β -glucans extracted from Saccharomyces cerevisiae increased the growth performance of piglets [11]. Additionally, Li and Kim reported an increase in BW and feed intake in growing pigs fed with SCCWE, attributed to its beneficial effect on lactic acid bacteria [7].…”
Section: Discussionmentioning
confidence: 99%
“…Kogan and Kocher found that SCCWE polysaccharides (mainly β -glucan) can modulate immunity and the absorption of mycotoxin, prevent the adhesion and dissemination of bacteria, and finally improve the health of pigs [10]. Additionally, Sweeney et al showed that oral administration of β -glucans extracted from Saccharomyces cerevisiae increased the growth performance of piglets [11]. Additionally, Li and Kim reported an increase in BW and feed intake in growing pigs fed with SCCWE, attributed to its beneficial effect on lactic acid bacteria [7].…”
Section: Discussionmentioning
confidence: 99%
“…The higher sodium content of seaweed relative to land plants (Philippsen 2013;Ruperez 2002) and limited digestibility of many seaweed proteins and carbohydrates (McHugh 2003) may restrict its use as a feed. A number of substances in seaweed have been found to have animal nutritional and health benefits (Holdt and Kraan 2011;McHugh 2003;Sweeney et al 2012), and seaweed could have considerable further potential for the supply of animal and aquaculture nutritional supplements.…”
Section: Fertiliser and Animal Feedmentioning
confidence: 99%
“…Successful infection by pathogens depends on subversion of host immune mechanisms that detect cell wall components such as fucans (Berteau and Mulloy 2003) and glucans (Rappleye et al 2007). Glucans from the macroalgae, L. hyperborean and L. digitata as well as those from baker's yeast, S. cerevisiae, are all reported to decrease the number of Enterobacteriacea in pigs (Sweeney et al 2012). The medicinal uses of a number of compounds from marine sources have recently been reviewed: glycans (Pomin 2014), glycolipids (Plouguerné et al 2014) and sulphated polysaccharides and fucoidans (Wijesinghe and Jeon 2012).…”
Section: Therapeutic Productsmentioning
confidence: 99%
“…A study compared the effects of purified beta-glucans derived from L. digitata, L. hyperborea, and Saccharomyces cerevisiae on piglet performance, selected bacterial populations, and gut short chain fatty acid production (Sweeney et al, 2012). However, all beta-glucans do not act on the same manner.…”
Section: Different Species May Have Different Effectsmentioning
confidence: 99%